Methylation dependent gold adsorption behaviour identifies cancer derived extracellular vesicular DNA. Issue 9 (12th June 2020) - Sina, Abu Ali Ibn; Lin, Ting-Yun; Vaidyanathan, Ramanathan; Wang, Zhaoran; Dey, Shuvashis; Wang, Jing; Behren, Andreas; Wuethrich, Alain; Carrascosa, Laura G.; Trau, Matt
Abstract : Methylation dependent gold adsorption behaviour of extracellular vesicular DNA enables liquid biopsy test for cancer. Abstract : Extracellular vesicles (EV) play a major role in intercellular communication by transmitting cellular materials ( e.g. protein, RNA) among distant cells. Recent evidence suggests that they could also contribute to carrying DNA which could inform on the mutational status of the parent tumour DNA. Thus, the fundamental analysis of evDNA could open a better understanding of tumour metastasis and provide new pathways for noninvasive detection and monitoring of cancer. To explore the potential of evDNA for diagnostics, the isolation of pure evDNA from body fluids free of cfDNA contamination is crucial. Herein, we use a liposome based model system to develop an improved evDNA isolation protocol free from cfDNA contamination and evaluate the methylation dependent physicochemical properties of evDNA to develop a simple test for detecting cancer evDNA. Using a highly sensitive multiplex microelectrode device, we demonstrate that serum-evDNA derived from cancer patients show different solution and surface based properties than normal evDNA due to their different methylation landscape ( i.e. methylscape). This microdevice allows simultaneous analysis of multiple samples in a single platform from as low as 500 pg μL −1 of evDNA.